ETHICAL ASPECTS IN TREATING ADOLESCENTS WITH CHRONIC DISEASE - SZTANKOVSZKY, Laszlo-Zoltan; IORGA, Magdalena (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
Chronic disease during the period of adolescence demands a lot of specific issues dues to the particular psychological, physical and social development of this stage. Patient-doctor relationship, communication, medical consultation, information, sharing an uncomfortable diagnostic with parents or involving the family in the treatment should be carefully approach. Privacy, confidentiality and informed consent are ethical aspects that must be also taken into consideration. The management of the chronic disease during adolescence become a great challenge to the medical team. The practice of adolescence medicine is always a challenge to resolve ethical dilemmas.